1999 sonrası Türkiye’de uygulanan ekonomik istikrar politikaları neticesinde mali sürdürülebilirlik - Göktan, Alper (My University, 2008)
İstikrar politikalarının performansı ülke ekonomilerinin devamında temel öneme sahiptir. Bu çalışmada Türkiye’de uygulanagelen mali istikrar ve mali sürdürülebilirlik politikaları 1999 – 2006 yıllarına odaklanılarak irdelenmiştir. Literatürde mali sürdürülebilirlik için hem kaynaklar hem de harcamalar üzerinde yoğunlaşılmıştır. Türkiye’de mali sürdürülebilirliğe ilişkin olarak; uygulamada kullanılan durağanlık ve ko-entegrasyon testleri ile Türkiye için geçerli olan sürdürülebilirlik koşullarına bakılarak 1999 sonrasında uygulanan mali politikaların borçlanma için sürdürülebilirliği sağlayıp sağlamadığı araştırılmıştır. Mali sürdürülebilirlik için literatürde sıklıkla kullanılan durağanlık ve ko-entegrasyon testleri sonucunda, 1999-2006 döneminde uygulanan mali politikaların borçların sürdürülebilirliğini sağlamakta yetersiz kaldığı bulunmuştur.

The performance of the stability policies plays a key role in the continuity of the economies of the countries. This study examines the financial stability and financial sustainability policies that have been executed in Turkey, focusing on 1999 – 2006. The literature review majors on both resources and expenses for financial sustainability. Whether the financial policies implemented in Turkey after 1999 satisfies the sustainability of borrowing is investigated based on the stagnancy and co-integration tests, which are used in the application part of the study performed for financial sustainability applied on the current sustainability conditions in Turkey. Most of the applied analyses have shown that the borrowing may be sustainable if the ratio of debt stock to the national income stays constant in the long run. As a result of main tests used in the literature for financial stability, which are stagnancy and co-integration, the financial policies implemented on 1999 – 2006 have been inadequate to satisfy the sustainability of the borrowings.
Keywords: Ekonomik Gelişim; İstikrar Politikası_Türkiye; Maliye Politikası